Mulheres em situação de violência sexual: redes de atenção e relatos da experiência sofrida - Cara, Anderson Tiago de [UNESP] (2015)
This is study, in first stage, uses documentary-quantitative method and aims to verify from the Epidemiological Monitoring of data query obtained from the Information System database and Notifiable Deseases (SINAN) from 2009-2012, rates of cases of women in situations of violence reported in Bauru/SP. General information regarding the records were collected notified in SINAN, identifying the type of violence, sociodemographic data, the consequences for the victims and referrals made to service agencies, only women aged over 18 years. Data were organized, coded and submitted to Estatistic Binomial test. In the second stage, carried out case studies in order to investigate the experiences of four participants regarding suffered sexual violence and consequences, as well as their perception of the aspects that contributed to the overrun or not this life event. This sample was obtained through hospital records Reference Service and Woman's Center on Violence Situation (CRAMSV) with thirty-two cases have been identified, which, subject to the eligibility criteria and the study resulted in ten cases and these four cases that could participate. The interviews were conducted individually after a call and ethinical procedures, using the Bardin's method (1977) for the analysis of the interviews. Results indicated predominance of physical violence (60.89%) followed by sexual violence (21.14%) and most women had the age of 18, low level of education and that only a minority of cases received appropriate referrals to the network of municipal service. We also observed the lack of follow-up mechanisms of the reported cases. Showed up significant deficiencies in the data record of the reported cases, obscuring the reality of the situation of violence against women, despite the notification by the SINAN. The conclusion is thus that the episode of sexual violence suffered by participants in this study showed physical and psychosocial consequences